1988
DOI: 10.3109/01485018808987050
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Characteristics of Nuclear Proteins from Human Spermatozoa

Abstract: A comparative electrophoretic analysis of nuclear proteins was investigated in ejaculated human semen. The results confirm the biochemical heterogeneity of nucleoproteins in sperm with normal routine parameters and demonstrate the same heterogeneity in semen with defective routine parameters: nucleoproteins comprise histones, intermediate proteins, and protamines in the two groups. Individual qualitative and quantitative differences are observed within and between the two groups. The results allow a better kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 9 publications
2
4
0
1
Order By: Relevance
“…In this way our experiments supplement the results of Lescoat et al (1988). In the case of the examination of sperm nucleoproteins, various falsifications are possible by aggregations or proteolysis of proteins, and further by contamination with other proteins than sperm nucleus non-protamines.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In this way our experiments supplement the results of Lescoat et al (1988). In the case of the examination of sperm nucleoproteins, various falsifications are possible by aggregations or proteolysis of proteins, and further by contamination with other proteins than sperm nucleus non-protamines.…”
Section: Discussionsupporting
confidence: 73%
“…Examinations of nucleoproteins of single ejaculates revealed very different electrophoretic patterns: some semen samples showed an electrophoretic distribution of spermatozoa1 nucleoproteins as described by other authors (Puwaravatipanich and Panyim -1975;Pongsawasdi and Svasti -1976;Tanphaichitr et al -1982;Lescoat et al -1988): Protamines HPS 1/2, H P 1, HP 2, H P 3, HP 4 and afew slight bands like histones. Other semen samples hardly showed protamines whereas more bands could be seen which were slower than HPS 1, the non-protamines.…”
Section: Electrophoretic Patterns Of Nucleoproteins Of Various Semen supporting
confidence: 61%
“…In man, male infertility has been associated with both decreased levels of protamines (Silvestroni et al 1976;Chevaillier et al 1987;Lescoat et al 1988;Blanchard et al 1990;Sakkas et al 1996;Ziyyat et al 1999) and increased Prm1-to-Prm2 ratios Belokopytova et al 1993). Recently, Steger et al (2001) compared the fertilizing capacity of spermatozoa gained by testicular sperm extraction (TESE) and followed by intracytoplasmic sperm injection (ICSI) with the percentage of round spermatids in the corresponding biopsy exhibiting Prm1-mRNA and Prm2-mRNA.…”
mentioning
confidence: 99%
“…Anomalies in the protamine content in infertile patients were already described more than 20 years ago [12,[154][155][156]. Subsequently, studies further confirmed the association of abnormal protamine content with abnormal seminal parameters and male infertility [14,15,21,35,[157][158][159][160][161][162][163][164][165].…”
Section: Protamine Anomalies In the Sperm Cells Of Infertile Patientsmentioning
confidence: 53%